The making of a pan‐European organ transplant registry. (31st December 2012) - Smits, Jacqueline M.; Niesing, Jan; Breidenbach, Thomas; Collett, Dave
Summary A European patient registry to track the outcomes of organ transplant recipients does not exist. As knowledge gleaned from large registries has already led to the creation of standards of care that gained widespread support from patients and healthcare providers, the European Union initiated a project that would enable the creation of a European Registry linking currently existing national databases. This report contains a description of all functional, technical, and legal prerequisites, which upon fulfillment should allow for the seamless sharing of national longitudinal data across temporal, geographical, and subspecialty boundaries. To create a platform that can effortlessly link multiple databases and maintain the integrity of the existing national databases crucial elements were described during the project. These elements are: (i) use of a common dictionary, (ii) use of a common database and refined data uploading technology, (iii) use of standard methodology to allow uniform protocol driven and meaningful long‐term follow‐up analyses, (iv) use of a quality assurance mechanism to guarantee completeness and accuracy of the data collected, and (v) establishment of a solid legal framework that allows for safe data exchange.